2023
DOI: 10.3390/pathogens12040621
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Control of Dendrobium officinale Bud Blight Disease

Abstract: Dendrobium officinale is an important traditional Chinese medicine (TCM). A disease causing bud blight in D. officinale appeared in 2021 in Yueqing city, Zhejiang Province, China. In this paper, 127 isolates were obtained from 61 plants. The isolates were grouped into 13 groups based on collected areas and morphological observations. Four loci (ITS, LSU, tub2 and rpb2) of 13 representative isolates were sequenced and the isolates were identified by constructing phylogenetic trees with the multi-locus sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In order to verify the pathogenicity of the isolated fungi, according to Zhang’s method with small modification [ 18 ], the leaves and branches were put on a moist sterile filter paper in Petri dishes, a 7 × 7 mm mycelium plug was placed on the wounded leaves, and the sterile PDA was placed on the wounded leaves as the controls. The dishes were incubated in a growth chamber under artificial light (12/12 h light/dark) at 30 °C and 80% humidity, and the symptoms were observed after 5–7 days.…”
Section: Methodsmentioning
confidence: 99%
“…In order to verify the pathogenicity of the isolated fungi, according to Zhang’s method with small modification [ 18 ], the leaves and branches were put on a moist sterile filter paper in Petri dishes, a 7 × 7 mm mycelium plug was placed on the wounded leaves, and the sterile PDA was placed on the wounded leaves as the controls. The dishes were incubated in a growth chamber under artificial light (12/12 h light/dark) at 30 °C and 80% humidity, and the symptoms were observed after 5–7 days.…”
Section: Methodsmentioning
confidence: 99%
“…10,11 Oxine-copper, an organic copper fungicide widely used in agricultural production, was found to exhibit good protective and curative effects on angular leaf spot either as a single active ingredient or as a component of a mixture in the field. 12,13 It was effective against most bacterial diseases and some fungal and viral diseases. 14,15 After application, oxine-copper tended to evenly cover the plant surface and slowly release copper ions, which can effectively inhibit the germination and invasion of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Oxine-copper, an organic copper fungicide widely used in agricultural production, was found to exhibit good protective and curative effects on angular leaf spot either as a single active ingredient or as a component of a mixture in the field. , It was effective against most bacterial diseases and some fungal and viral diseases. , After application, oxine-copper tended to evenly cover the plant surface and slowly release copper ions, which can effectively inhibit the germination and invasion of bacteria. , Oxine-copper is widely used in China on crops such as pears, apples, cucumbers, watermelons, and tomatoes . The dissipation of oxine-copper in citrus, apple, pear, loquat, bayberry, and river water has been studied, and the results indicated that the degradation of oxine-copper by different crops was different.…”
Section: Introductionmentioning
confidence: 99%